2017
DOI: 10.1097/qai.0000000000001544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Schooling on Age-Disparate Relationships and Number of Sexual Partners Among Young Women in Rural South Africa Enrolled in HPTN 068

Abstract: Background Attending school may have a strong preventative association with sexually transmitted infections among young women, but the mechanism for this relationship is unknown. One hypothesis is that students who attend school practice safer sex with fewer partners, establishing safer sexual networks that make them less exposed to infection. Setting We used longitudinal data from a randomized controlled trial of young women age 13-20 in the Bushbuckridge district, South Africa, to determine if the percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Indeed, adolescent involvement in sports, clubs, and other organizations (either in school or extracurricular groups) can provide young people with a sense of meaning or belonging and has been associated with better health outcomes, including improved sexual health . Youth engagement in activities would also bring increased social contact with other youth, and therefore could also imply more protective sexual networks with less time to venture outside of those safer networks (for example with older partners who are more likely to be infected) . It is also possible that this domain is synergistic with leadership, in that communities with more accountable and inclusive leadership may also have more opportunities for organizations and networks to thrive, both of which contribute to (and are fortified by) having a more engaged citizenry.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adolescent involvement in sports, clubs, and other organizations (either in school or extracurricular groups) can provide young people with a sense of meaning or belonging and has been associated with better health outcomes, including improved sexual health . Youth engagement in activities would also bring increased social contact with other youth, and therefore could also imply more protective sexual networks with less time to venture outside of those safer networks (for example with older partners who are more likely to be infected) . It is also possible that this domain is synergistic with leadership, in that communities with more accountable and inclusive leadership may also have more opportunities for organizations and networks to thrive, both of which contribute to (and are fortified by) having a more engaged citizenry.…”
Section: Discussionmentioning
confidence: 99%
“…Associations with frequency of school attendance in young women indicate that spending more time in school may impose time and sexual network constraints that reduce exposure to infection, and that these reductions may or may not be related to school performance. More research is needed to better understand the mechanism by which education reduces risk of HIV and HSV-2, but other analyses from our study in South Africa indicate that school attendance affects partner selection including both partner age difference and number of sexual partners [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Almost all villages in the study area have a high school. The most common reason for school drop out is being pregnant or having a child and the most common reason for low attendance is being sick or disabled followed by having to help at home [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Another study that used the same dataset found that school enrolment in 2002 was associated with a reduced rate of later sexual debut, although this was only statistically significant in boys [168]. A recent study in Mpumalanga province found that girls who had dropped out of school had 1.85 times as many sexual partners as girls of the same age who did not drop out of school, although this study did not specifically assess sexual debut or control for possible confounding due to pregnancy-related dropout [169]. The evidence therefore suggests that being in school reduces the chance of starting sexual activity, but it is less clear whether educational attainment affects sexual debut, after controlling for age and current school enrolment.…”
Section: Sexual Behaviourmentioning
confidence: 99%
“…The evidence therefore suggests that being in school reduces the chance of starting sexual activity, but it is less clear whether educational attainment affects sexual debut, after controlling for age and current school enrolment. Some evidence suggests that youth who are enrolled in school but with relatively low grade advancement have lower rates of sexual debut [88], while other evidence suggests the opposite [82], and some studies suggest no significant effect of grade repetition on sexual behaviour [166, 169].…”
Section: Sexual Behaviourmentioning
confidence: 99%